PERSPEKTIF REMAJA TERHADAP DAKWAH ONLINE STUDI EMPIRIS PADA SISWA MA HASANUDDIN SIRAMAN KESAMBEN BLITAR - Mumtahanah, Khoirul; Anfaul Umat, Wihda Ikvina (Universitas Muhammadiyah Jember, 2020)
Judging from the times, we will increasingly understand that life goes fast. Good filter ability is a key indicator that everyone must have in facing this development. This article is the result of research that leads to the development of the digital world, especially in the field of online that touches almost all aspects of life. One that attracts researchers is the entry of the online world into the realm of da'wah. Conventional da'wah is done face-to-face, now has experienced many shifts and shifts through online media with the intention of facilitating access. The purpose of writing this article is to analyze adolescent perceptions about online propaganda and preaching methods that are of interest to adolescents with empirical studies of MA students Hasanuddin Siraman, Kesamben, Blitar. This descriptive-qualitative article directly observes adolescents at MA Hasanuddin about their perceptions of online da'wah and the method of da'wah that appeals to adolescents. The selection of adolescents as research subjects is because researchers find data that users of the digital or online world are the most widely held by adolescents, so that indirectly adolescents have the possibility of accessing da'wah online. The method used for this research is observation, interview, and documentation. The data obtained will then be matched using data triangulation techniques to be able to obtain data validity. The results of this study in the form of adolescent perceptions of online propaganda and propaganda methods are in demand by adolescents in this millennial era